Governança global da segurança alimentar e fragmentação do direito internacional - Dias, Thais Ferreira Ivo (2021)
Solving the problem of hunger and malnutrition in the world depends not only on legal measures, but also on economic, geopolitical, political and social measures, that is, it permeates a series of complex and fluid relations between state and non-state inter-national organizations, state policies, norms and political actions, called global food security governance. The search for these solutions began in an organized and institutionalized way, since 1945, with the creation of the Food and Agriculture Organization (FAO) and was progressively intensified, resulting in the so-called fragmentation of global governance. While some argue for the positivity of this expansion, others argue that such circumstances can be problematic, being this the perspective that will be analyzed in this dissertation. Therefore, the work will be divided into two chapters, the first being a historical reconstitution of the creation of international institutions relating their respective creations to moments of economic crisis and the second an analysis of the excerpts presented above, that is, the causes of the expansion governance and the lack of legal effectiveness of FAO's normative statements. The methods used were qualitative research and bibliographic research, and for the analysis of the lack of legal effectiveness of the FAO normative statements, a specific method described in the body of the dissertation was used. It was concluded, therefore, that the coexistence of scattered and inefficient attempts to solve the problem through the creation of multiple OIGs exacerbate the fragmentation of international law and, combined with the absence of coercive and sanctioning mechanisms characteristic of soft law, They are timid and insufficient for the effective resolution of a complex and multifaceted problem.